UMTS NETWORK DEVELOPMENT AND USE IN THE MANAGEMENT AND INFORMATION SYSTEM OF TRANSPORT (Perner's Contacts, 2011)
The article deals with the development of UMTS networks, evaluating the properties of public mobile networks, 3G (T-Mobile, Telefónica and Vodafone) on the basis of experimental measurements and the possibility of use in traffic control and information systems.
Keywords: HSDPA; HSPA; HSUPA; LTE; UMTS; response; connection speed; download; standard deviation